Institutionalizing mycotoxin testing in Africa - Waliyar, Farid; Siambi, M.; Jones, R.; Reddy, S.; Chibonga, D.; Kumar, L.; Denloye, S. (CAB International, 2008)
The aflatoxin class of mycotoxins is one of the most important food safety concerns at domestic and international levels. The widespread occurrence of aflatoxin contamination in Africa and other tropical countries is a major potential hazard to humans and domesticated animals, and causes severe health and economic problems. Africa is in a precarious position because the environmental conditions and cultural practices across the continent favor fungal attacks of crops and commodities. Other factors that exacerbate African problems include constraints in resources and infrastructure, a lack of adequate regulatory and control systems for monitoring mycotoxin contamination, and limited availability of food due to war, famine and other natural disasters. Several countries in Africa have established regulations on mycotoxins in food and feed to safeguard both health and trade interests. Due to inadequate facilities for monitoring mycotoxins, the institutionalization of food safety regulations in Africa has been difficult. The availability of accurate, cost-effective testing procedures for rapid mycotoxin analysis is a prerequisite for the enforcement of food safety regulations and to facilitate international trade. Recently, we established aflatoxin-testing facilities in Nigeria, Malawi, Mali and Mozambique. These facilities enable farmers and traders to make sales in the high-value international trade markets. In this chapter, we discuss the problems and opportunities for institutionalizing aflatoxin-testing facilities in Africa.